2020
DOI: 10.1186/s12976-020-00123-w
|View full text |Cite
|
Sign up to set email alerts
|

An agent-based model to investigate microbial initiation of Alzheimer’s via the olfactory system

Abstract: Background: Alzheimer's disease (AD) is a degenerative brain disease. A novel agent-based modelling framework was developed in NetLogo 3D to provide fundamental insights into the potential mechanisms by which a microbe (eg. Chlamydia pneumoniae) may play a role in late-onset AD. The objective of our initial model is to simulate one possible spatial and temporal pathway of bacterial propagation via the olfactory system, which may then lead to AD symptoms. The model maps the bacteria infecting cells from the nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Some viruses, like the herpes virus, can go dormant after the original infection and then reawaken decades later in elderly people, causing delayed harmful complications ( Nagarajan and Wilde, 2005 ). According to a 2020 study model, immunocompromised people who were exposed to C. pneumoniae through their noses developed Aβ plaque and NFTs in their olfactory cortex as well as in hippocampus ( Sundar et al, 2020 ). Thus antimicrobials such as Rifampicin, Amphotericin B, acyclovir, penciclovir, foscarnet etc.…”
Section: Drug Repurposing For Neurodegenerative Diseasesmentioning
confidence: 99%
“…Some viruses, like the herpes virus, can go dormant after the original infection and then reawaken decades later in elderly people, causing delayed harmful complications ( Nagarajan and Wilde, 2005 ). According to a 2020 study model, immunocompromised people who were exposed to C. pneumoniae through their noses developed Aβ plaque and NFTs in their olfactory cortex as well as in hippocampus ( Sundar et al, 2020 ). Thus antimicrobials such as Rifampicin, Amphotericin B, acyclovir, penciclovir, foscarnet etc.…”
Section: Drug Repurposing For Neurodegenerative Diseasesmentioning
confidence: 99%
“…C. pneumoniae , a respiratory pathogen, has specifically been suggested to enter the brain through the olfactory system, with its presence detected in the entorhinal cortex and hippocampal formation of AD patients [ 73 ]. A recent 2020 study model demonstrated that exposure to C. pneumoniae via the olfactory system was sufficient to induce Aβ plaque and NFT formation in the olfactory cortex and hippocampus of immunocompromised individuals [ 74 ]. This is further evidenced by Little et al, who found that intranasal inoculation of C. pneumoniae was sufficient to induce AD-like traits in mice [ 75 ].…”
Section: Antimicrobial Protection Hypothesismentioning
confidence: 99%
“…It must be noted, however, that the association between infection and Aβ plaque formation is not consistent across all populations. For example, in the study previously mentioned by Sundar et al, younger and healthier individuals exposed to C. pneumoniae did not exhibit the same AB peptide and NFT formation as older and immunocompromised subjects [ 74 ]. Moreover, it has been observed that genetic discrepancies, especially in the APOE gene, influence one’s susceptibility to HSV-1 infection and subsequent AD development.…”
Section: Antimicrobial Protection Hypothesismentioning
confidence: 99%
“…In a healthy situation, BBB provides a selective barrier to the passage of cells and molecules into the brain; however, in a pathological situation, a compromised BBB can allow direct entry into the brain through the passage of blood to the CSF ( 23 , 24 ). Moreover, pathogens, including bacteria and viruses can bypass the BBB by entering via the olfactory system, because the nasal cavity connects the peripheral environment to brain regions such as the olfactory bulb, the entorhinal cortex and the hippocampus ( 47 ). SARS-CoV-2 infection is widespread in epithelial cells, particularly in the lungs, starting its invasion and entry into the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%